Chemical and physical attributes in an anfisol cultivated with Panicum Maximum Jacq. cv. IPR-88 Milênio, under rotational stocking and fertilized with nitrogen - Sarmento, Patrícia; De Andrade Rodrigues, Luis Roberto [UNESP]; Da Cruz, Mara Cristina Pessôa [UNESP]; Lugão, Simony Marta Bernardo; De Campos, Fábio Prudêncio; Centurion, José Frederico [UNESP]; Ferreira, Manoel Evaristo [UNESP] (My University, 2008)
It is necessary to evaluate the soil physical and chemical attributes in studies that explore grazing systems intensively. In this work the variation in physical and chemical attributes of an Alfissol cultivated with Panicum maximum Jacq. cv. IPR-86 Milênio under grazing were evaluated from October 2001 to May 2002, in the fifth year of consecutive N application at rates of 0, 150, 300, and 450 kg ha-1. After five successive applications of 450 kg ha-1 N, the OM content increased 5 g dm3, which resulted in CEC increase. From October 2001 to May 2002 the pH and basis saturation degree decreased with the increasing N rates. The range in soil density with N fertilization was small; the micropore percentage increased and the macropore percentage decreased in the 0-5 cm layer with increasing N rates, but the total porosity remained constant; and the soil penetration resistance at 90 g ha -1 of water was not affected by N rates and was not restrictive to plant growth.
Atributos químicos e físicos de um argissolo cultivado com Panicum Maximum Jacq. cv. IPR-86 Milênio, sob lotação rotacionada e adubado com nitrogênio
Keywords: Soil density; Soil fertility; Soil penetration resistance; Soil porosity